Acoustic analysis of voicing contrast on Malay word-initial plosives produced by Tamil-speaking children - Preeta Rajandran; Badrulzaman Abdul Hamid (Penerbit Universiti Kebangsaan Malaysia, 2023)
The primary objective of this study was to investigate the acquisition of voicing contrast in Malay word-initial plosives produced by Tamil-speaking children. This study's contribution to the existing literature lies in adding information on Malay word-initial plosives produced by Tamil-speaking children which can be instrumental in developing objective speech evaluation and designing effective intervention plans in the speech-language pathology practice. A total of 15 subjects aged between 3;00 to 7;11 years old were included in the present study. The participants underwent a picture naming task, and their speech samples were recorded and acoustically analysed using PRAAT. Descriptive data were presented, and a non-parametric Mann-Whitney U test was conducted to examine gender effects on voice onset time (VOT) of Malay word-initial plosives produced by Tamil-speaking children. The results indicated that at the age of 3;00, children produced only short lag VOT values. By the age of 5 years old, Tamil-speaking children acquired the expected voicing contrast in Malay word-initial plosives (pre-voiced vs. short lag). Full acquisition of voicing contrast for Malay plosives (pre-voiced vs. short lag) was observed at the age of 7. The later acquisition of voicing contrast and pre-voicing was further discussed. VOT distributions aligned with the developmental path proposed by Macken & Barton (1980) and Zlatin & Koenigsknecht (1976). Notably, place of articulation effects on the duration of VOTs were not observed in Tamil-speaking children. This finding prompted considerations of perceptual, social, and environmental factors, as well as Cross-Linguistic Influence, as plausible reasons for this phenomenon. Furthermore, with increasing age, the VOT values tended to approach adult-like VOT patterns. Regarding gender effects, no significant gender differences in VOT of Malay word-initial plosives were found in Tamil-speaking children, except for the phoneme /d/. Possible explanations for this were discussed in detail.